The Prevalence of Burnout and Its Associated Factors Among Surgical Specialists in Kuwait Ministry of Health Hospitals - Akl, Amr; Mohiyaldeen, Idrees; Alshatti, Rashed; Alenezi, Omer; Dougherty, Ryan; Al-Raihan, Abdullah; Alotaibi, Salman; Tadros, Nardine; Longenecker, Joseph C. (Frontiers in Public Health, 2022)
Background Workplace burnout is a state of emotional exhaustion (EE), depersonalization of others (DP), and low personal accomplishment (PA) owing to workplace stressors. This study aimed to assess the prevalence of burnout and its associated factors among surgical specialists in Kuwait. Methods This cross-sectional study assessed the prevalence of burnout among 489 surgeons in practice at Kuwait Ministry of Health (MOH). Data were collected using a self-administered questionnaire. Burnout was assessed using the Maslach Burnout Inventory, which defines burnout as having a high score of EE or DP, or a low score of PA; with severe burnout involving all. The associations between burnout or severe burnout with sociodemographic and occupational characteristics were assessed using multivariate binary logistic regression to adjust for potential confounders. Results Prevalence estimates for burnout and severe burnout were 76.9% (95% Confidence .Interval. =72.9–80.7%) and 14.0% (11.0–17.5%), respectively. The prevalence estimates for high EE, high DP, and low PA scores were 44.7%, 43.1%, and 47.2%, respectively. The prevalence of burnout and severe burnout was highest among neurosurgeons. Burnout was lowest among otolaryngology surgeons and severe burnout was lowest among cardiothoracic surgeons. After adjustment, burnout was associated with younger age, lower income, and more on-calls per month. The four most common sources of stress included less family time, verbal assault, case overload, and highly complicated cases. Conclusion The prevalence of burnout among surgeons in Kuwait MOH hospitals is high. Occupational health programs should use these findings to design and implement interventions that can treat and prevent burnout in this population.